Large‐Area Flexible Memory Arrays of Oriented Molecular Ferroelectric Single Crystals with Nearly Saturated Polarization. Issue 45 (26th September 2022) - Xu, Mingsheng; Sheng, Chenxu; Zhang, Qiuyi; Zhou, Xiaojie; Tian, Bobo; Chen, Luqiu; Cai, Yichen; Li, Jianping; Wang, Jiao; Xie, Yongfa; Qiu, Xinxia; Wang, Wenchong; et al.
Abstract: Molecular ferroelectrics (MFs) have been proven to demonstrate excellent properties even comparable to those of inorganic counterparts usually with heavy metals. However, the validation of their device applications is still at the infant stage. The polycrystalline feature of conventionally obtained MF films, the patterning challenges for microelectronics and the brittleness of crystalline films significantly hinder their development for organic integrated circuits, as well as emerging flexible electronics. Here, a large‐area flexible memory array is demonstrated of oriented molecular ferroelectric single crystals (MFSCs) with nearly saturated polarization. Highly‐uniform MFSC arrays are prepared on large‐scale substrates including Si wafers and flexible substrates using an asymmetric‐wetting and microgroove‐assisted coating (AWMAC) strategy. Resultant flexible memory arrays exhibit excellent nonvolatile memory properties with a low‐operating voltage of <5 V, i.e., nearly saturated ferroelectric polarization (6.5 µC cm −2 ), and long bending endurance (>10 3 ) under various bending radii. These results may open an avenue for scalable flexible MF electronics with high performance. Abstract : Large‐area uniform flexible memory arrays with molecular ferroelectric single crystals (MFSCs) are demonstrated using an asymmetrical wetting and microgroove‐assisted coating strategy. The well‐oriented micrometer‐scale MFSCs can ensure a high performance of nonvolatile memory functions with a nearly saturated polarization of 6.5 µC cm −2 (approaching their spontaneous values), low‐operating voltages of <5 V, and long bending endurance of >10 3 .